The use of cannabinoid compounds in therapy in children - future or threat? - Joanna Cieszkowska; Julia Czerwik; Marta Czubala; Joanna Dmochowska; Jakub Kamiński (Kazimierz Wielki University, 2023)
Introduction and objective: Therapy with the use of "medical marijuana" is becoming more and more popular with patients, who often perceive it as a more natural and safe form of treatment. It is also more and more boldly considered by physicians in the pediatric population, especially when standard methods of pharmacotherapy prove insufficient. The following review focuses on the possibilities of using cannabis preparations in children with drug-resistant epilepsy, autism spectrum disorders and spasticity. It also draws attention to the possible side effects and risks of unjustified use of medical marijuana. State of knowledge: In the pediatric population, high efficacy and a favorable safety profile have been proven so far in the treatment of epileptic seizures associated with Lennox-Gastaut syndrome and Dravet syndrome, and for the treatment of epileptic seizures in tuberous sclerosis complex, (TSC) . Although the therapy has been approved only for the above-mentioned indications, high hopes are also placed on the use of cannabinoids to treat the symptoms of other diseases and disorders, including spasticity and autism spectrum disorders. Conclusions: The research carried out so far gives hope for the possibility of using medical marijuana in other indications as well, as its use correlates with the reduction of i.a. symptoms of spasticity or autism spectrum disorders. At the same time, further studies are needed to assess the balance of benefits and potential risks of the therapy. Since recreational cannabis use in youth is known to be associated with serious adverse events,  and medical cannabis use has a relatively strong placebo effect, decisions about its use should always be made carefully and based on scientific evidence.